Optimizing the magnetic core structure of a multi-stack Switched Reluctance (SR) motor using finite-element modeling: article / Nurul Nadia Zoid - Zoid, Nurul Nadia (2013)
This proposal described the application of Finite Element Magnetic Method (FEMM) on analysis of optimizing the magnetic core structure of a multi-stack switched reluctance motor (SRM). The motor stack is modeled in Finite Element Magnetic Method (FEMM) package and the performance parameter computed such as inductance, resistance, flux linkage, voltage drop and etc. The pole widths of the stator is varied in steps to search for the optimum rotor pole width for a given stator pole width. After that flux linkage over current and rotor position versus torque index are plotted. The process is repeated for other stator pole widths until both optimum stator and rotor pole widths are obtained.